HOW SAFE IS ON-LABEL DRUG USE IN PAEDIATRICS? THE CASE OF FIRST GENERATION H1-ANTIHISTAMINES. Issue 1 (14th December 2015) - Bruyne, Pauline De; Boussery, Koen; Christiaens, Thierry; Mehuys, Els; Winckel, Myriam Van
Abstract : Background: For obvious reasons, much attention has recently been paid to off-label prescriptions in paediatrics. However, on-label prescribing can cause health issues too: we discuss the case of first generation H1-antihistamines (FGAs). These have been in use for over 70 years, for a variety of indications such as relief of allergic conditions, cough and insomnia. Materials and methods: The FGAs were listed using their International Nonproprietary Names (INN). For each formulation, the information of the Summary of Product Characteristics issued in five selected European countries (Belgium, France, Germany, the Netherlands and United Kingdom) was collected. This was plotted against the published evidence on efficacy and safety of each FGA. Results: 16 different FGAs are currently marketed in single-drug oral preparations in the evaluated countries. When investigating each drug separately, a huge variability in labelled indications, licensing age for paediatric use, and availability characteristics in the different countries is observed. Most of the indications are not supported by evidence from published clinical trials. Conclusion: Both health care professionals and consumers generally assume that all approved H1-antihistamines have been shown to be efficacious and safe, but many in this class – in particular those introduced before 1985 – have not been optimally studied. This might explain the inconsistencies in indications and licensing ages of the evaluated drugs in different countries. Moreover, many of the antihistamines are sold over the counter, which may contribute to overuse. Such overuse can be a serious problem, as sedation is a known side effect of all FGAs.